2015
DOI: 10.1021/acs.langmuir.5b01419
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting by Nickel Prussian Blue Analogue Electrode in Neutralization and Mixing Entropy Batteries

Abstract: Some industries usually reduce the concentration of protons in acidic wastewater by conducting neutralization reactions and/or adding seawater to industrial effluents. This work proposes a novel electrochemical system that can harvest energy originating from entropic changes due to alteration in the concentration of sodium ions along wastewater treatment. Preparation of a self-assembled material from nickel Prussian blue analogue (NPBA) was the first step to obtain such electrochemical system. Investigation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
0
27
0
2
Order By: Relevance
“…67,68 An electrode consisting of silver particles dispersed in PPy (Ag/PPy) was prepared and used as the negative electrode in a MEB system. 61 A full cell consisting of NiHCF (positive) and Ag/PPy (negative) electrodes afforded 16.8 kJ per mol of sodium ion for each electrochemical cycle as demonstrated by charge/ discharge curves ( Figure 9). The negative electrode removed and provided chloride anions during the oxidation and the reduction processes, respectively.…”
Section: Polypyrrole (Ppy)mentioning
confidence: 99%
See 2 more Smart Citations
“…67,68 An electrode consisting of silver particles dispersed in PPy (Ag/PPy) was prepared and used as the negative electrode in a MEB system. 61 A full cell consisting of NiHCF (positive) and Ag/PPy (negative) electrodes afforded 16.8 kJ per mol of sodium ion for each electrochemical cycle as demonstrated by charge/ discharge curves ( Figure 9). The negative electrode removed and provided chloride anions during the oxidation and the reduction processes, respectively.…”
Section: Polypyrrole (Ppy)mentioning
confidence: 99%
“…In fact, Gomes et al 61 used thin NiHCF films to check the applicability of PBA in MEB. The average anodic and cathodic peak potentials relative to the potential measured for the electrolytic 20 mM NaCl solution as a function of the molar concentration logarithm demonstrated that it is possible to use this electrode to convert energy from a highly saline water source (Figure 8a): the authors extracted 12.4 kJ per mol of sodium ion after a charge/ discharge cycle, which is equivalent to the area between the discharge curve in a 3.0 M NaCl aqueous solution and the charge curve in a 20 mM NaCl aqueous solution (Figure 8b).…”
Section: Prussian Blue Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…proposed a pseudocapacitor based on the ion intercalation/de‐intercalation mechanism for energy‐harvesting and employed transition metal oxides as cation electrodes with Ag for the anion electrode to enhance the performance of this pseudocapacitor. Other cation electrodes have also been studied, such as hexacyanoferrate compounds . However, this battery‐like approach is challenged by the gradual leaching loss of Ag, which is an expensive material with limited availability.…”
Section: Figurementioning
confidence: 99%
“…Other cation electrodes have also been studied, such as hexacyanoferrate compounds. [17][18][19] However, this battery-like approachi sc hallenged by the gradual leachingl oss of Ag, which is an expensive material with limited availability.R ecently,Y oon et al [20] proposed an asymmetric capacitor that used sodium manganese oxides and AC as electrodes and ion-exchange membranes,w hichr esulted in an expensive device.Ah ybrid capacitor, [21][22][23] also known as as econd-generation supercapacitor that typically couples insertion-and adsorption-type electrodes and combines two charge-storage mechanisms,h as attracted much attention becauseo fi ts high energya nd powerd ensities.A ccordingly,t his concept has been introduced into capacitive deionizationf or desalination. [24] In this work, we propose ac ost-effective technique called "hybrid capacitive mixing" (HCM) that extracts SGE without using expensivem embranes or Ag.…”
mentioning
confidence: 99%